Study on Inclusion Complex of b-Cyclodextrin-Dithizone-Zinc (b-CD-H2Dz-Zn) by Spectrophotometry and Its Analytical Application - Mohamad, S.; Mohd Kamal, S.N.R. (Asian Journal of Chemistry, 2012)
The non-covalent interaction of b-cyclodextrin and dithizone-zinc (H2Dz-Zn) complex was studied by spectrophotometry. The results showed that b-cyclodextrin formed a complex with H2Dz-Zn in a ratio of 1:1 with an apparent formation constant of 4.7 × 102 M-1. Due to the enhancement of absorbance intensity of dithizone-zinc produced from complex formation, a spectrophotometry method was developed for determination of zinc in the presence of b-cyclodextrin. A linear relationship between absorbance and concentration of zinc was obtained in the range of 0.1-9.0 mg/L with correlation coefficient of 0.996. The detection limit obtained was 0.005 mg/L and the relative standard deviation (RSD) was 2.05 %. The developed method was applied in real samples and the recoveries obtained were from 85-95 %.